Macro-Level Social Work Interventions in Schools: Poverty Simulation Programs as Professional Development Opportunities for K–12 Educators. Issue 2 (25th February 2023) - Curry, Anna Maria T; Tomczak, Stephen Monroe
Abstract: Poverty continues to be a significant public health crisis across the United States, and its impact is particularly prevalent among school-aged youth and their families. Many K–12 educators do not fully understand the realities associated with living in poverty. Such a lack of understanding impacts teachers' ability to meet the unique educational needs of students experiencing poverty and develop positive teacher–student relationships. This article sets the stage for further discussion on the lack of quality training, education, and professional development for teachers on poverty. The authors propose a model for professional development aimed at increasing empathy and understanding among K–12 educators through experiential learning tools such as the Community Action Poverty Simulation. The article concludes with an in-depth discussion on implications for future practice and a call to action for school social workers to bring innovative solutions to their campuses that pull from their educational background in advocacy and social justice to enhance teacher training through an interdisciplinary approach.